Understanding the occurrence and fate of microplastics in the Arctic fjords of Svalbard - Purver, Madeleine Lydia Susan, 1992- (2019)
Verkefnið er lokað til 28.05.2020. The full impact and costs of microplastics are yet unknown, although public awareness, as well as financial awareness, are arising. The main aim of this project was to gain more understanding of microplastic pollution fate and occurrence in the surface waters of Arctic fjords in western Svalbard, including investigations into whether atmospheric long-range transport plays an important role in the transport of microplastics to the Arctic. Isfjorden, Svalbard was chosen as the main sampling area since it contains fjord arms with different features although all fjords are within a reasonable distance. Samples were collected in five of the fjords, three with little traffic and visitors (Ekmanfjorden, Dicksonfjorden and Nordfjorden) and two fjords containing settlements (Grønfjorden; Russian settlement Barentsburg and Adventfjorden; Norwegian settlement Longyearbyen). Samples were taken from the mouth of the fjord to catch riverine and glacial inputs as well as the impact from the local settlements when present. A river, Oxaasdalen, draining into Dicksonfjorden, was also sampled. The samples were collected using a manta net, and also a high-capacity pump system with metal filters. All fjords sampled contained microplastics, with an average 0.57 ± 0.07 MP/m3. Polyethylene was the most common polymer, found in all fjords except Nordfjorden. Of all the microplastic particles identified in this study 63% were found to be fibres. The river Oxaasdalen contained the highest MP/m3 of all sample sites (4), indicating the need for further research into long-range atmospheric transport. Since microplastics have been found in the ‘pristine’ Arctic, it illustrates how contaminants can impact remote locations and not just highly populated areas. Next, this global problem will need to be addressed at the source; shifting to a circular economy to lessen the impact of single use plastic.